FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN PASIEN PRE OPERATIF SEKSIO SESARIA - ", Deswita "; Dewi, Yulia Irvani; Nauli, Fathra Annis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Cesarean section (SC) is an artificial labor in which the fetus is born through an incision in the front wall of the abdominal and uterine walls with the terms of the uterus intact. This study aims to determine the factors associated with patient anxiety level Pre-Operative cesarean section. This design was descriptive correlation research with cross sectional approach. This study used acctidential sampling there were 30 respondents. This study used quesioners about knowledge, family support and anxiety questionnaire Hamilton Anxiety Rating Scale (HARS). The analysis used univariate analysis to determine the frequency distribution and bivariate using Kolmogorof Smirnov test. The results Kolmogorof Smirnov statistical test results prove that there is a relationship between the level of knowledge of the patient's preoperative anxiety SC p value = 0.050 <α (0.05), the family support there is no relationship between family support (p = 0.464) and the economic aspects (p = 0.083), so it can be concluded that good knowledge can reduce anxiety levels. The results of this study are expected to be input for the patient to be able to play an active role in gaining insight into the SC, the family will be expected to provide support and a comfortable atmosphere, and for the institution where the research is expected to apply the results of this study in order to reduce the anxiety level of the patient's pre-operative SC. Keywords: Anxiety level, economic, Fammily support, knowledge